The impact of professional doctorates in the workplace: evidence from the criminal justice sector. Issue 3 (3rd July 2021) - Creaton, Jane
ABSTRACT: This study explores the impact of professional doctorates in the workplace in the specific context of the criminal justice sector, through a qualitative study of practitioners who have graduated from professional doctorates in criminal justice and security risk management. A thematic analysis of semi-structured interviews with 25 graduates was undertaken to identify the nature and extent of impact on their workplaces. The study suggests that professional doctorates may potentially have a significant impact on the workplace, but the actual extent is shaped by three interrelated factors: the motivations of students, the role of their employer and the nature of the programme in which they are enrolled. The article concludes with a discussion of the implications for how institutions could design and deliver professional doctorate programmes in order to extend workplace impact.